Association of Essential Tremor With Dementia and Affective Disorders: A Meta-Analysis - Shang, Yajun; Chen, Xinjie; Ai, Mingda; Gao, Xiaoran; Dai, Shujuan; Zhao, Mingjie; Yang, Cen; Wang, Liangfeng; Zhang, Junyan; Zhong, Lianmei; Bao, Tianhao; Liu, Xiaolei (Frontiers in Neurology, 2022)
Background The dementia and affective disorders are common non-motor features in patients with essential tremor (ET). However, the relationship of ET with cognitive impairments and affective disorders remains controversial. This meta-analysis aimed to analyze the association of ET with dementia and affective disorders. Methods Original studies published from January 1999 to October 2019 were systematically searched from the database of Medline (OvidSP), EMBASE (OvidSP), and the Cochrane Central Register of Controlled Trials. Pooled standard mean difference (SMD, random effect model), odds ratios (ORs), relative risk (RR), and 95% CI were calculated. Results Compared with the Non-ET group, patients with ET had significantly lower Mini-Mental State Examination (MMSE) score (SMD, −1.16; 95% CI, −1.75 to −0.58; p = 0.0001) and had significantly higher depressive and anxiety symptoms scale score (SMD, 0.55; 95% CI, 0.22–0.87; p = 0.0009). The OR for dementia and affective disorders in individuals with ET compared with individuals without ET was 2.49 (95% CI, 2.17–2.85, p < 0.00001). While there was no significant difference in Montreal Cognitive Assessment (MoCA) score between ET and Non-ET groups (SMD, −0.52; 95% CI, −0.16 to 0.13; p = 0.23), there was a significant difference in the risk of mortality between ET and Non-ET groups (RR = 4.69, 95% CI, 2.18–10.07). Conclusion The non-motor symptoms should not be neglected among patients with ET. However, the causal relationship between ET and dementia, depression, and anxiety is unclear.